Sifat Mekanik Beton Dengan Crumb Rubber Sebagai Bahan Tambah Pada Beton Serat Perkerasan Kaku - Ilham Sordiman; Monita Olivia; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study examines the effect of crumb rubber on the mechanical properties of rigid pavement fiber concrete as an added material to increase the flexibility of rigid pavements. The specimens were tested mechanically such as compressive strength, tensile strength and flexural strength for 7, 14 and 28 days. The results showed that optimum compressive strength occurred at a percentage of 2% crumb rubber, but for the effectiveness of using rubber waste without sacrificing the compressive strength of the plan using a percentage of 4% crumb rubber. The value of the compressive strength of concrete PCC Normal and PCC +4% crumb rubber experienced a steady increase. The value of PCC +4% split tensile strength crumb rubber showed lower results than normal PCC concrete. PCC +4% concrete flexural strength of crumb rubber has a higher value than normal PCC concrete. Based on the results of these tests it was concluded that PCC +4% concrete crumb rubber had mechanical properties on increasing compressive strength which remained stable and better flexural strength, but the tensile strength showed a decrease in normal PCC concrete. Keywords: Crumb rubber, fiber concrete, rigid pavement, PCC, mechanical properties